2009
DOI: 10.2746/042516408x363800
|View full text |Cite
|
Sign up to set email alerts
|

Influence of foot conformation on duration of competitive life in a Dutch Warmblood horse population

Abstract: This study provided evidence that the conformation trait uneven feet has a negative effect on Warmblood jumping performance and, therefore, breeders should be encouraged to avoid this phenomenon at foal age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 11 publications
2
28
0
Order By: Relevance
“…The results are partly supported by a study of Dutch Warmbloods, where mares had a higher risk of culling from basic dressage. However, no gender differences were found in elite dressage or basic/elite jumping [17]. Similar to the present study, a study of flexion test reactions of 100 clinically sound horses indicated that mares obtained significantly more post flexion test reactions compared to geldings [16].…”
Section: Discussionsupporting
confidence: 81%
“…The results are partly supported by a study of Dutch Warmbloods, where mares had a higher risk of culling from basic dressage. However, no gender differences were found in elite dressage or basic/elite jumping [17]. Similar to the present study, a study of flexion test reactions of 100 clinically sound horses indicated that mares obtained significantly more post flexion test reactions compared to geldings [16].…”
Section: Discussionsupporting
confidence: 81%
“…Stock and Distl (2005) found that the prevalence of radiographie findings on young horses sold in auctions influenced the number of later participations in competition, even if there was no effect on successful participation. Duero et al (2009) found a negative effect of uneven feet on the duration of competitive life especially in Elite Jumping (risk ratio 0.52 for even feet). All these reports showed the importance of limb conformation, which may be detected at an early stage, for the longevity of horses.…”
Section: Selectionmentioning
confidence: 95%
“…Across both racing and equestrian sports, the active career of the equine athlete is relatively short, with the median career length being 2-3 years for a racehorse (Tanner et al, 2011(Tanner et al, , 2012) and 3-4 years for eventing, show jumping, and dressage horses (Rogers and Firth, 2005;Ducro et al, 2009;Friedrich et al, 2011). The major reason for loss of horses from equestrian sports, or racing, is musculoskeletal injury (Jeffcott et al, 1982;Wallin et al, 2000;Perkins et al, 2005;Wilsher et al, 2006).…”
Section: Wastage In Equestrian Sportsmentioning
confidence: 96%